2019
DOI: 10.32601/ejal.651387
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Listening Comprehension in L1 and L2: A Meta-analysis

Abstract: The present meta-analysis aimed to explore the correlates of listening comprehension in first (L1) and second language (L2). In this regard, the overall average correlation scores, obtained from several primary studies retrieved from several databases, between linguistic (vocabulary size, vocabulary depth, syntactic knowledge), cognitive (working memory, metacognitive skills), and affective factors (anxiety and self-concept) and oral comprehension were measured. The results of the analysis revealed that in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
3
3
1
Order By: Relevance
“…For the relationship between metacognitive awareness and L2 listening, we found that metacognitive awareness explained listening to a small degree (Research Question 2). The results accord well with those of previous studies (e.g., Goh & Hu, 2014;Karalık & Merç, 2019) and suggest the limited importance of metacognitive awareness to listening. The results were moderated by publication type, the response format of listening comprehension tests, and participant type.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…For the relationship between metacognitive awareness and L2 listening, we found that metacognitive awareness explained listening to a small degree (Research Question 2). The results accord well with those of previous studies (e.g., Goh & Hu, 2014;Karalık & Merç, 2019) and suggest the limited importance of metacognitive awareness to listening. The results were moderated by publication type, the response format of listening comprehension tests, and participant type.…”
Section: Discussionsupporting
confidence: 92%
“…The proportion of variance explained was 9.364%, which was slightly smaller than the results from previous primary studies, for example, a correlation of 13% in Vandergrift et al.’s (2006) study, and a multiple regression coefficient of 22% in Goh and Hu's (2014) study. Our results were slightly larger than those from previous meta‐analyses, compared, for example, to 3.881% (.197 × .197 in Table 1; Karalık & Merç, 2019). As we produced our results using MASEM while considering measurement error and testing the model‐data fit, they would be more tenable than the previous results.…”
Section: Discussioncontrasting
confidence: 89%
See 2 more Smart Citations
“…Regarding the investigation of a correlation between linguistic competence and listening comprehension in the current study, the result shows a positive linear relationship between linguistic competence and listening comprehension. This corresponds to the findings of some other studies (Oh & Lee, 2014;Karal?k & Merç, 2019) showing that there are relative contributions of linguistic competence to L2 listening comprehension. Although linguistic competence significantly correlates with listening comprehension, it has only a small influence on listening comprehension due to the covariance of 16.4 per cent out of all factors involved in listening success.…”
Section: Instrumentssupporting
confidence: 90%